Perbandingan Metode Titrasi Asidi-alkalimetri Dengan Titrasi Iodometri Dalam Analisis Formalin Pada Sampel Tahu Putih Kecamatan Gondanglegi, Kabupaten Malang - Suriaman, Edi; Eryatma, Rosalinda Avia; Ma’rufah; Zulaikah , Siti; Mahdiasanti, Ika Wuri (Fakultas Kedokteran, Universitas Palangka Raya, 2024)
This study aimed to compare two titration method (acid-base titration and iodimetri) in analyze formaldehyde at sample tofu in Gondang legi sub-district, Malang District. The research used a experimental method with added variation concentration formaldehyde in tofu filtrate. Tofu filtrate with formaldehyde then be titrated with acid-base and iodimetri method. Acid-base titration used Phenolphtalein (PP) indicator and Iodimetri titration used amylum indicator. The results of study the higher the concentration of formaldehyde the volume of titration. Titration used Iodimetri method not recommended because redox reaction at iodimetri is a slow and inaccurate reaction.